The Analysis of Self Regulated Learner of Acceleration Class at Secondary School in Natural Science Subjects Based on Gender - Novia Dwi Rahmaningtyas; Septi Budi Sartika; Nuril Maghfiroh (Postgraduate, University of Mataram, 2023)
The purpose of this research is to describe the self-regulated learner (SRL) of male and female accelerated students. The research method used is qualitative phenomenology research conducted at SMP Negeri 1 Sidoarjo. The research focused on one male student and one female student of accelerated class. Data collection techniques used in the research included observation, questionnaire and interview techniques. From the data obtained, data analysis was carried out using three stages including data reduction, data presentation and conclusion drawing.Â The results of the research obtained SRL of male and female students lead to academic and non-academic fields, and have unequal abilities in science subjects. Male SRL indicators that are not achieved are organization and seeking help while female SRL indicators that are not achieved are anxiety tests. The factor that influences the non-achievement of SRL indicators is that students are less able to manage organization, seek help and test anxiety on themselves. Future research is expected to develop learning tools to train students' SRL.